Climate change mitigation with Eurobonds: an Environmental Kuznets Curve analysis - Richard Fosu Amankwa; Eric B. Yiadom; Evans Acheampong; John K. M. Mawutor (Cogent Economics & Finance, 2024)
This study examines the impact of Eurobonds on carbon dioxide emissions in Africa using a panel dataset. The paper reconsidered the Environmental Kuznets Curve (EKC) and integrated it into Eurobond Environmental Kuznets Curve (EEKC). This study modelled a panel dataset spanning from 2007 to 2018 using all 17 sovereign African countries that have issued Eurobonds. The findings highlight a significant scientific value in exploring Eurobonds as a financing option to reduce carbon dioxide emissions in Africa. Specifically, the study reveals a positive relationship between Eurobond issuance and carbon dioxide emissions at the initial stage of the EEKC. By including the square term of Eurobond, the research identifies the existence of the EEKC in Africa, which supports the EKC theory. These results contribute to the growing body of literature on climate change mitigation and financing strategies in the context of African economies. Moreover, this study fills a critical void in the literature by introducing Eurobonds into the climate financing debate, emphasizing their potential role in financing climate-resilient activities. The study recommends that the issuing of Eurobonds should be linked to climate resilient activities, enabling funds to be directly invested in green sectors of the economy. This novel perspective on Eurobonds as a tool for environmentally sustainable projects adds scientific significance to the discourse on climate finance and sustainable development in Africa. The paper "Climate Change Mitigation with Eurobonds: An Environmental Kuznets Curve Analysis" presents a groundbreaking examination of Eurobond issuance's impact on carbon emissions in African countries. By integrating the Environmental Kuznets Curve theory with Eurobond financing, it uncovers insights into Eurobonds' potential for climate change mitigation and sustainable development. This research contributes significantly to climate finance and environmental sustainability discussions by analyzing panel data from 2007 to 2018 across 17 African nations. Initially, Eurobond-funded projects increase carbon emissions, in line with the Environmental Kuznets Curve hypothesis. However, as economies progress, Eurobonds correlate with reduced emissions, suggesting the emergence of an "Eurobond Environmental Kuznets Curve." These findings offer vital guidance for policymakers, advocating for aligning Eurobond issuance with environmental goals and promoting eco-friendly projects. They emphasize the importance of tailored policies that evolve with African countries' economic growth stages, alongside investments in education, domestic initiatives, and environmentally-conscious foreign direct investment. This research lays the groundwork for informed decision-making in climate finance and sustainable development strategies, vital for steering towards more environmentally sustainable paths.
Keywords: 330; Eurobonds; climate change; Environmental KuznetsCurve; carbon dioxide emissions; Eurobond Environmental Kuznets Curve; random effect regression model